Women's Experiences of Diagnosis and Disclosure of Borderline Personality Disorder: A Narrative Inquiry - McDonagh, Teresa Joan (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2025)
Background: Since the borderline personality disorder diagnosis (BPD) diagnosis was first introduced in 1980 its use has continued to increase. Even as critical debates rage regarding its validity and utility, both inside and outside of psychiatry where it was first constructed, it continues to be used in biomedically dominated systems to individualise, medicalise, and label distress, firmly locating the disorder in the person independent of their social context. 75% of people diagnosed with BPD are women, their voices and experiences of diagnosis and disclosure of BPD therefore need to be better heard and understood. Aim: The aim of this inquiry was to explore the lived experiences of women in receiving the diagnosis of BPD, or emotionally unstable personality disorder (EUPD), in the Irish context, to gain an understanding of the meaning they attach to that diagnosis. The inquiry furthermore aimed to garner an understanding of the experiences of women in disclosing their diagnosis to others. Methodology: A narrative inquiry methodology that draws on feminist and critical perspectives was employed. Participants consisted of 14 women diagnosed with BPD/EUPD who were resident in the Republic of Ireland. Data were gathered using in-depth narrative interviews. The narrative analysis was conducted using a dual-level analytic strategy employing the Listening Guide (LG) and a Reflective Thematic Analysis (RTA). Findings: The synthesised findings developed through the RTA enhanced the accessibility of the narrative findings translating them into three main themes. The themes identified include: life before being diagnosed as "borderline:" women's early life experiences; the diagnostic moment: women's stories of being diagnosed with BPD/EUPD, and; life after diagnosis: women's stories of disclosure and living with the diagnosis of BPD/EUPD. Dyadic relationships were identified as an overarching concept in the narratives. Conclusions: The unique contribution of this inquiry is its focus on the women's voices as they navigate their lived experience of life before the diagnosis of BPD, the diagnostic moment, and life after the diagnosis living with the borderline label. Within each stage the voices of the women illuminate potential points of intervention that will inform the practice of mental health nursing and other disciplines, policy, education, and research.
APPROVED
Keywords: borderline personality disorder; narrative inquiry; mental health; diagnosis; disclosure; stigma; listening guide; power threat meaning framework